Case report and the surgical treatment of two cases with pulmonary atresia in which pulmonary arteries is circulated by coronary arteries - Kahraman Yakut; Kürşad Tokel; Birgül Varan; Ilkay Erdoğan; Murat Özkan (KARE Publishing, 2018)
Pulmonary atresia (PA) and ventricular septal defect (VSD) can occur in a variety of ways, from simple valve atresia to a condition in which circulation to the pulmonary bed occurs through collateral arteries separated from the aorta and there are no real pulmonary arteries, or they are present but hypoplastic. The size of the pulmonary arteries and concomitant complex cardiac lesions are important in making decisions about treatment and correctional alternatives. While complete correction surgeries in the style of a correction of tetralogy of Fallot are performed in simpler cases, many very invasive procedures are also performed and the resulting quality of life is very variable. The size of the pulmonary artery and its branches and the presence of accompanying collateral vessels are determining factors in the management of the disease. In this report, 2 cases of VSD and PA, in which the circulation of the pulmonary arteries was through the coronary arteries, diagnosed as a result of echocardiography performed following murmurs heard during examination, are described. The first patient was 40 days old and the second was 2 days old. In the second case, diagnosis was confirmed by catheter angiography, and in the first case, the final diagnosis was made during surgery. The aim of this report is to emphasize the importance of pulmonary artery size, the presence of pulmonary confluence, the origin of circulation, and concomitant collateral arteries when considering treatment methods.